Albert Pujols - Brenner, Richard J., 1941- (New York : Scholastic Inc., 2007)
Albert Pujols is the most feared hitter in the National League. He has received the National League Rookie of the Year Award, 2003 batting title, 2005 Most Valuable Player Award, and led the St. Louis Cardinals to the 2006 World Series championship.
"First Scholastic printing, April 2007"--T.p. verso.
Keywords: Pujols, Albert, -- 1980- -- Juvenile literature; Baseball players -- United States -- Biography -- Juvenile